Application of Cytogenetic Indicators for Bioindicative Assessment of the Environmental Status of Territories Exposed to Radiation - Lozinskaya, Olga V.; Knyazeva, Zlata (Journal of the Belarusian State University. Ecology, 2026)
The significance of biological control in the environmental monitoring system is analyzed. A special role is noted in biomonitoring programs for the search and use of bioindicators that allow a reliable assessment of the environmental situ-ation depending on the degree of impact of various anthropogenic factors. It indicates the ability of some species of plants and animals to respond sensitively at the genetic and morphological level to changes that occur, as well as their suitability for assessing various territories. Data are provided on the assessment of the ecological status of territories by cytogenetic test reactions (frequency of aberrations) of the phyto-indicator – onions (Allium cepaL.), cultivated on water extracts of soils of natural and anthropogenically modified territories. It has been shown that the soils of the biosphere reserve have a weak mutagenic effect, where the total frequency of aberrations was in the range from 9 to 13%. Thus, the soils of the territory of the BelNPP environs have a moderate mutagenic effect – the frequency of aberrations ranged from 9 to 17%,and the observed frequency of mitosis disturbances on the soils of the exclusion zone was in the range of 20–29%. It has been established that the degree of soil contamination of the studied ecologically diverse territories determines the direction of the process of mitosis. The nature of the change in bioindicational indicators depending on the elemental composition of soils (in particular, the presence of heavy metals and radionuclides) was revealed. Analysis of the obtained data confirmed the reliability of theAllium-test method for assessing territories and the possibility of its application in the environmental monitoring system. Based on this, 3ecologically unequal clusters were identified, differing in the degree of anthropogenic inﬂuence. The first is the territory with radiation pollution – the Polesie State Radiation-Ecological Reserve (PSRER), the second is the anthropogenically disturbed territory–BelNPP and the third is the reference territory – the Berezinsky Bio-sphere Reserve with aminimum level of pollution.